The aristocats [videorecording (Blu-Ray + DVD)] - Clemmons, Larry, 1906-1988; Bruns, George (Buena Vista Home Entertainment, 2012)
In Paris, a kind and eccentric millionairess wills her estate to Duchess, her cat, and her three kittens. When her greedy butler attempts the ultimate catnap caper, the alley cat Thomas O'Malley and his band of jazz cats must save the day.